1987
DOI: 10.2134/agronj1987.00021962007900030034x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Residue Management Effects on Properties of an Ultisol and Double‐Cropped Soybean Production1

Abstract: Doublecropping soybean (Glycine max (L.) Merrill) and wheat (Triticum aestivum L.) has become widespread in the southeastern United States. This has encouraged use of reduced and no-tillage systems, but burning of the wheat straw prior to planting soybean has also become common. A 2-yr field study was initiated on a Greenville sandy clay loam (Rhodic Paleudult) in Georgia to evaluate effects of tillage and residue management practices on selected soil properties and plant growth parameters. Main experimental b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 10 publications
4
28
0
Order By: Relevance
“…However, later cover.toP ffig ,gs will maximize residue dry matter production, promoting subsequent soil water conservation (Moschler et al 1967)' Field studies have shown that straw rates higher than 3 Mg ha-l signifrcantly increased soil water storage of mulched plots wf,en compared to bare soil plots (Aase and Tanaka tg8Zl. While increases in soybean yields due to soil water conservation by plant residues have been reported in some studies (Webber-et al 1987;Edwards et al 1988), other studies have encountered no yield differences (Elmore 1987;NeSmith et al 1987). Decreases in yields observed in no-till soybeans have not been associated with the lower soil temperaoies ttrat occur under no-tillage systems (Tollner et al 1984 (Weston 1990 Fehr et al (1971).…”
mentioning
confidence: 98%
“…However, later cover.toP ffig ,gs will maximize residue dry matter production, promoting subsequent soil water conservation (Moschler et al 1967)' Field studies have shown that straw rates higher than 3 Mg ha-l signifrcantly increased soil water storage of mulched plots wf,en compared to bare soil plots (Aase and Tanaka tg8Zl. While increases in soybean yields due to soil water conservation by plant residues have been reported in some studies (Webber-et al 1987;Edwards et al 1988), other studies have encountered no yield differences (Elmore 1987;NeSmith et al 1987). Decreases in yields observed in no-till soybeans have not been associated with the lower soil temperaoies ttrat occur under no-tillage systems (Tollner et al 1984 (Weston 1990 Fehr et al (1971).…”
mentioning
confidence: 98%
“…Extractable water in double-cropped plots, in contrast, was not affected by soybean row spacing. Wheat residue mulch protected plot surfaces and probably reduced evaporation and surface sealing equally for both soybean row spacings (NeSmith et al, 1987). Double-cropped narrow-row soybean plots often contained less extractable water in the last half of the 1982 and 1983 seasons than monocropped narrow-row soybean plots, data in Table 2 being representative.…”
Section: Interactionsmentioning
confidence: 97%
“…This finding suggests that wheat residue increased infiltration and /or reduced evaporation from double-cropped plots in comparison to monocropped plots. NeSmith et al (1987) found that winter wheat residue as a mulch on the soil surface increased soil water contents in the upper 10 cm of the profile by limiting evaporation, increasing infiltration, or reducing water use.…”
Section: Interactionsmentioning
confidence: 99%
“…Crops with a well-developed rooting system are expected to have less water stress than those with shallow roots. NeSmith et al (1987) reported that soybeans extracted more water from the 15-to 45-cm depth of CT (moldboard plow and disk) systems than disk tillage or NT systems. Water stress becomes critical when there is limited rainfall during grain development and grain-filling stages (Wagger and Denton 1992).…”
Section: Silage Corn and Soybean Yieldsmentioning
confidence: 99%